Azza Eyewear Business Development Strategy Using Swot Analysis - Putri, Feronika Panggih; Pahlevi, Reza Widhar (PT FORMOSA CENDEKIA GLOBAL, 2023)
Azza eyewear is a type of business that provides goods such as glasses, contact lenses and women's wallets. This research approach uses a SWOT analysis approach. The SWOT analysis aims to take advantage of strengths, weaknesses, opportunities and threats as a form of business strategy development carried out by Azza Eyewear. Data collection techniques using direct observation through interviews with owners, employees and some consumers as informants. The interview results obtained were then analyzed to determine the strengths, weaknesses, opportunities and threats as a form of business development strategy carried out by Azza Eyewear. The results show that Azza eyewear has the power to make existing business opportunities. The business development strategy is carried out by offering quality products at competitive prices and increasing sales promotions with social media technology Instagram, Facebook Marketplace and Whatsapp Business